Strategi Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Kendari Dalam Meningkatkan Kualitas Pelayanan Perizinan - Alnur, Nurlaila; Justawan, Justawan; Taufik, Taufik (Universitas Halu Oleo, 2020)
This study aims to find out and describe the Strategy of the Investment Office and One Stop Services in the City of Kendari.Â The research method used is descriptive qualitative research, a description of the results of interview observations and documentation studies, so as to be able to describe various matters relating to the Strategy of Improving the Quality of Licensing Services Data that has been obtained are analyzed qualitatively and described in descriptive form. The results showed that the DPMPTSP strategy in improving the quality of licensing services in terms of the competence of the apparatus, SOP and SPM, facilities and infrastructure had been running quite well but the implementation was not optimal and had not shown the maximum results needed to be increased in the provision of training, service providers still pay attention to proceduresÂ prevailing as well as service recipients, the lack of available facilities, in terms of improving service quality in terms of the dimensions of reliability, responsiveness, assurance, empathy, and physical products as a whole have tried to do as much as possible even though there are still employees / service providers who have notÂ find out about licensing completely.